Influence of guanxi on hospitality career performance in China: Is more necessarily better?. (October 2020) - Ren, Shuang; Chadee, Doren
Highlights: Careers in hospitality are inevitable embedded in interpersonal relationships. We distinguish developing and maintaining guanxi behaviors in their roles related to hospitality career performance. We challenge the linear association commonly assumed between guanxi and career outcomes of hospitality employees in China. Developing guanxi initially enhances hospitality career performance up to a point after which it has negative implications. Maintaining guanxi positively moderates the curvilinearity between developing guanxi and hospitality career performance. Abstract: Careers in hospitality are inevitably influenced by interpersonal relationships which, in China, are embodied in the unique cultural-relational phenomenon of guanxi. The study challenges the conventional wisdom that in China more guanxi is necessarily better for one's career by distinguishing between two distinct guanxi behaviors and investigating their effects on the career performance of hospitality employees. Using multi-source data from a sample (n = 351) of hospitality employees, the results show that behaviors for developing guanxi contribute positively to hospitality career performance up to an inflexion point, after which they turn negative. Behaviors for maintaining guanxi provide additional resources that can attenuate the negative influence of excessive guanxi development on career performance. The implications of the findings that more guanxi is not necessarily better for the career performance of hospitality employees are fully discussed, along with suggestions for future research and practice.